Agenesis of gallbladder-series of four cases - why it is difficult to diagnose preoperatively? - Biswarup Bose; Abhimanyu Basu; Subhadip Sarkar (Asian Journal of Medical Sciences, 2023)
Agenesis of gallbladder (AGB) is a rare clinical entity first reported by Bergman in 1702. The incidence is about in 10–65 cases/1,00,000 population. It is seen in 1/6th cases of biliary atresia. It is of unknown etiology and is believed to be due to abnormal embryonic development. Nearly 70% cases are sporadic. AGB may be associated with other congenital abnormalities including the biliary system. The majority (nearly 50%) of the patients are symptomatic with misinterpreted signs and symptoms of cholecystitis and lands up to unnecessary surgery. Our series of four cases have male: female ratio of 3:1. Two of the cases underwent laparoscopic surgery. Among the other two, one had biliary pancreatitis due to primary calculous in the common bile duct (CBD) with upstream dilation. Other cases had chronic pancreatitis with dilated pancreatic duct and a proximal calculous close to ampulla causing proximal dilation of CBD. Two operated cases were postoperatively diagnosed by magnetic resonance cholangiopancreatography (MRCP) and the non-operated patients were also diagnosed by MRCP. Symptomatic AGB is often wrongly interpreted as cholecystitis with cystic duct obstruction or as sclero-atrophic gallbladder, therefore leading to pointless surgical interventions. In case of false-positive ultrasonography (USG) of AGB, it has been suggested that either a loop of gas-containing bowel located in the gallbladder fossa or periportal tissue and subhepatic peritoneal folds impersonate a contracted gallbladder containing gallstones. When USG reveals such reports or in cases of non-visualization in other imaging modalities, the need of additional preoperative imaging investigation must be in the surgeon’s mind such as MRCP to avoid surgery which is not at all required.